2020
DOI: 10.3389/fnins.2020.554018
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Cardiac Structural and Functional Adaptations After Lumbosacral Spinal Cord Epidural Stimulation and Task-Specific Interventions: A Pilot Study

Abstract: Cardiac myocyte atrophy and the resulting decreases to the left ventricular mass and dimensions are well documented in spinal cord injury. Therapeutic interventions that increase preload can increase the chamber size and improve the diastolic filling ratios; however, there are no data describing cardiac adaptation to chronic afterload increases. Research from our center has demonstrated that spinal cord epidural stimulation (scES) can normalize arterial blood pressure, so we decided to investigate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…14,15,40 Alternatively, the inability to activate the sympathetic nervous system and/or lower-limb motor function during exercise may preclude an effective stimulus for measurable cardiovascular effects, given the growing evidence that sympathetic activation may be necessary for cardiac and vascular adaptation. 56,57 To specifically address the important role of the autonomic system, future studies should consider the influence of “autonomic completeness” on the cardiac and vascular adaptations to PA interventions in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,40 Alternatively, the inability to activate the sympathetic nervous system and/or lower-limb motor function during exercise may preclude an effective stimulus for measurable cardiovascular effects, given the growing evidence that sympathetic activation may be necessary for cardiac and vascular adaptation. 56,57 To specifically address the important role of the autonomic system, future studies should consider the influence of “autonomic completeness” on the cardiac and vascular adaptations to PA interventions in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated the efficacy and the mechanisms of spinal cord epidural stimulation (SCES) in enhancing motor recovery, 4 and restoration of standing and volitional overground stepping 5–7 . Furthermore, multiple reports show that SCES is effective in modulating lumbosacral neural circuits to regulate BP in persons with complete SCI 8–10 . Potential mechanisms of SCES‐induced regulation of orthostatic hypotension and cardiovascular function have been proposed 11,12 .…”
Section: Figurementioning
confidence: 99%
“… 5 , 6 , 7 Furthermore, multiple reports show that SCES is effective in modulating lumbosacral neural circuits to regulate BP in persons with complete SCI. 8 , 9 , 10 Potential mechanisms of SCES‐induced regulation of orthostatic hypotension and cardiovascular function have been proposed. 11 , 12 This may include increasing the resting membrane potential of the sympathetic circuitry via the stimulation of dorsal afferent relays, modulating local efferent outflow of spinal sympathetic neurons, changes in hormonal and inflammatory profiles, or vasodilation induced by antidromic stimulation of the afferent terminals.…”
mentioning
confidence: 99%
“…Lumbosacral spinal cord epidural stimulation (scES) combined with intensive activity-based recovery training is one such neuromodulatory approach that re-engages existing spinal circuits below the level of injury, challenging the novel postinjury circuitry to reorganize in functionally and physiologically signi cant ways [12][13][14][15][16][17]. Capitalizing on the inherent functional capacity that comprises these systemic circuits, scES enables autonomic circuits to recover signi cant levels of function [18][19][20][21][22][23][24][25][26][27]. We have previously shown that scES can be used to augment the lumbosacral neural circuitry below the level of injury su cient to potentiate gains in bladder function [21] achieved through activity-based recovery interventions alone [8,28].…”
Section: Introductionmentioning
confidence: 99%